PENGARUH PEMASARAN KERELASIAN TERHADAP KEUNGGULAN BERSAING UNIT BISNIS CARGO PT GARUDA INDONESIA - Marina, Sandriana; Hanifah, Hanifah; Agusinta, Lira (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
This study aims to determine the effect of marketing relationship on competitive advantage in Cargo Business Unit PT Garuda Indonesia. The research method used was descriptive verification with data analysis using simple linear regression. Primary data was collected through a survey of forty questionnaires distributed directly and online to the customers which is freight forwarding companies operating in the Soewarna Office and Warehousing Area, Soekarno Hatta Airport, Jakarta. The result of this research shows that the relationship marketing effects positive and significant to the competitive advantage of Cargo Business Unit PT Garuda Indonesia. Competitive advantage not only influenced by relationship marketing but influenced by other factors for further research. The results of this study suggest extending unit analysis to studying competitive advantage.